Self-efficacy development in School Principal Enhancement Programs - Albor, Rufo Gil Z.; Quimbo, Maria Ana T.; Santillana, Carolina P.; Dizon, Josefina T. (2012)
This mixed methods study aimed to describe the elements in Principal Enhancement Programs; identify specific elements in Principal Enhancement Programs which contributed to the self-efficacy of principals; identify unplanned experiences during the Principal Enhancement Programs which contribute to self-efficacy development. A total of 21 randomly selected principals from a municipality in Southern Tagalog Region of the Philippines were identified as eligible respondents for this study. They rated the effectiveness of their Principal Enhancement Programs and their self-efficacy. Principals with highly rated Principal Enhancement Programs and self-efficacy were chosen for qualitative interviews. Principal Enhancement Programs were perceived to be most effective in encouraging collegial relationships and self-reflection practices, promoting policy or procedure knowledge and practiced supervision. The Spearman Correlation Analysis showed that instructions, relevancy of coursework to practice and field experience elements were significantly associated with self-efficacy. Interview transcripts revealed that instructional experiences and leadership experiences before principalship are crucial to self-efficacy. Interview transcripts revealed that instructional experiences and leadership experiences before principalship are crucial to self-efficacy development. To purposely create efficacy-building experiences, Principal Enhancement Programs should design experiences that cause students to work with other people; develop extensive field experiences; and make leadership experiences; and, make leadership experiences prerequisite to principalship.
Keywords: Leadership; Education; Learning